The Effect of the Parameters of a Vibration-Based Impact Mode Piezoelectric Power Generator - Amat A. Basari; S. Awaji; S. Sakamoto; S. Hashimoto; B. Homma; K. Suto; H. Okada; H. Okuno; K. Kobayashi; S. Kumagai (Shock and Vibration)
This study reports the effects of the parameters of a vibration-based impact mode piezoelectric power generator. First, an evaluation of the effects of the impact parameters, the mass, and the impact velocity is presented. It is found that the output voltage of the piezoelectric device in impact mode is directly proportional to the velocity, whereas the output power is equal to a quadratic function of the same variable. For the same impact momentum, the effect of the velocity in generating a higher peak output is dominant compared with the mass. Second, the vibration-based impact mode piezoelectric power generator is discussed. The experimental results show that a wider operating frequency bandwidth of the output power can be achieved with the preloading configuration. However, regarding magnitude, due to the high velocity of impact, the configuration with a gap between the tip and the piezoelectric device produces a higher output.